The Musical Devil Revisited: Vercelli Homily X and Satan’s Fiddle - Heckman, Christina M. (Religion and the arts, 2023)
This article argues that modern examples of the Devil as a player of plucked and bowed stringed instruments extend early medieval representations of the Devil’s music as a powerfully persuasive force that can be used to draw souls toward Satan and, conversely, to defend against his musical machinations. By examining Homily X of the Vercelli Book (c. tenth century) in relation to early medieval music theory, the legend of St. Dunstan, and modern examples of the fiddle-playing Devil, this article demonstrates that the musical Devil and his opponents show every sign of sustaining the motif’s power into the future.